Adsorption Characteristics of Methyl Orange onto Different Adsorbents - H. Abdel Salam, Ahmed; H. Abd El Maksod, Islam; A. Shaker, Medhat; M. Faidallah, Hassan (Asian Journal of Chemistry, 2015)
In this work, batch experiments were conducted to test the adsorptive properties of a synergistic composite made of activated carbon coupled with titanium dioxide, alumina, silica or Saudi white sand silica. The created integrated adsorbent was proved to adsorb methyl orange dye better than the two separate ingredients of integrated adsorbent. Methyl orange was chosen as a model organic pollutant in the environment that has the potential to cause health risks for humans and biota. Adsorption studies indicated that synergism or inhibition occur in the composite adsorption capacity depending on the integrated adsorbent composition compared to the single adsorbents.